H/D reactivity and acidity of Bronsted acid sites of MWW zeolites: Comparison with MFI zeolite - Bulánek, Roman; Kubu, Martin; Vaculík, Jan; Cejka, Jiri (Elsevier Science BV, 2019)
Acid site strength in MWW and MFI zeolites was investigated by isotopic exchange reaction between deuterated hydroxyl groups of zeolites and ethane molecules. The course of the reaction was monitored by FT-IR spectroscopy through time changes of integral intensities of the Si(OD)Al Bronsted acid sites represented by absorption bands at 2644, 2655, and 2657 cm(-1) for MFI, MWW and MCM-36 zeolite, respectively. The rate of the reaction was described by pseudo first order kinetics and acid site strength was compared using rate constants characteristic of individual zeolites at constant temperature. The exchange reaction is significantly faster over MFI zeolite compared with MWW zeolites, suggesting a higher acid strength of Bronsted sites in MN zeolite than in MWW. In our previous study (Arean et al. Phys. Chem. Chem. Phys. 16 (2014) 10,129), we found notable discrepancy in the relation between OH group frequency shift induced by adsorption of weak base molecules like CO and N-2 and the change of adsorption enthalpy of these probe molecules for MWW zeolites, which calls into question the use of frequency shifts as a measure of acidity. Our reported results based on isotopic exchange reaction rate measurement correlate with the change of the probe molecules adsorption enthalpy involved in hydrogen bonding. Therefore, we believe that enthalpy change or H/D exchange activity measurement is more reliable method for assessment of acid strength than O-H frequency shift probed by a weak base adsorbed at a low temperature.
H/D reaktivita a kyselost Bronstedových kyselých poloh v MWW zeolitech: Srovnání s MFI zeolity
Keywords: Acidity; Zeolites; MWW; MFI; Isotopic exchange; Adsorption enthalpy; kyselost; zeolity; MWW; MFI; izotopická výměna; adsorpční entalpie